The new approaches to relations of atherosclerosis and Chlamydia pneumoniae [Chlamydia pneumoniae ateroskleroz ilişkisinde yeni yaklaşimlar] - (:unkn) unknown (My University, 2007)
The obligate intracellular bacterium Chlamydia pneumoniae is one of the pathogens that have been linked to atherosclerosis. Serological studies found association between specific IgA, IgG, IgM, circulating chlamydial immuncomplexes and atherosclerosis. Studies using with techniques such as immunocytochemistry, the polimerasc chain reaction, and culture showed that Chlamydia pneumoniae more common in atherosclerotic vessels rather than in normal vessels. The trials where patients with unstable angina or myocardial infarction were given macrolide antibiotics reported beneficial effects in terms of reduction of further coronary events. Although the pathogenic mecanisms linking C. pneumoniae infection to atherosclerotic disorders have still not been fully explained, different mecanisms have been suggested: 1- The studies demonstrated that TNF, IL-1, and endotoxin increased by an infection can induce a state of insulin resistance, 2-The proatherogenic effects of Lp(a) may be enhanced and/or partly mediated through the formation of circulating immune complexes containing C. pneumoniae-specific IgG antibodies. 3- The immune response to bacterial infectionm generally may interact with chlamydial or human heat shock proteins in vessel walls, so exacerbating atherosclerosis. Our hypothesis is that infection plays a role in only a subset of patients with coronary artery disease. Cronic C. pneumoniae infection might [aggravate the atherogenesis.
Keywords: Atherosclerosis; Chlamydia pneumoniae